Molecular mechanisms and functions of pyroptosis in sepsis and sepsis-associated organ dysfunction - Wen, Ri; Liu, Yong-Ping; Tong, Xiao-Xu; Zhang, Tie-Ning; Yang, Ni (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis, a life-threatening organ dysfunction caused by a dysregulated host response to infection, is a leading cause of death in intensive care units. The development of sepsis-associated organ dysfunction (SAOD) poses a threat to the survival of patients with sepsis. Unfortunately, the pathogenesis of sepsis and SAOD is complicated, multifactorial, and has not been completely clarified. Recently, numerous studies have demonstrated that pyroptosis, which is characterized by inflammasome and caspase activation and cell membrane pore formation, is involved in sepsis. Unlike apoptosis, pyroptosis is a pro-inflammatory form of programmed cell death that participates in the regulation of immunity and inflammation. Related studies have shown that in sepsis, moderate pyroptosis promotes the clearance of pathogens, whereas the excessive activation of pyroptosis leads to host immune response disorders and SAOD. Additionally, transcription factors, non-coding RNAs, epigenetic modifications and post-translational modifications can directly or indirectly regulate pyroptosis-related molecules. Pyroptosis also interacts with autophagy, apoptosis, NETosis, and necroptosis. This review summarizes the roles and regulatory mechanisms of pyroptosis in sepsis and SAOD. As our understanding of the functions of pyroptosis improves, the development of new diagnostic biomarkers and targeted therapies associated with pyroptosis to improve clinical outcomes appears promising in the future.